In vitro effects of two pulp capping materials (mineral trioxide aggregate and calcium hydroxide) on mononuclear leukocyte apoptosis - (:unkn) unknown (My University, 2013)
Mineral trioxide aggregate (MTA) and calcium hydroxide Ca(OH)2 are two common materials used in dental capping. In this study, we examined the apoptotic effects of these capping materials on human mononuclear leukocytes. Human mononuclear leukocytes were purified from peripheral blood by Ficoll-Hypaque gradient separation methodology. MTA and Ca(OH)2 specimen pastes were prepared freshly according to manufacturer instructions, and dried in a humidified CO2-containing incubator at 37 °C. Purified mononuclear leukocytes were treated with dried 1, 10, or 100 mg of both specimen pastes. May-Griinwald Giemsa staining and light microscopy were used to detect the apoptotic cells which were 4.87, 5.21, and 5.36%, respectively, for Ca(OH)2 pastes, and 4.25, 5.01, and 5.20%, respectively, for MTA specimens. Only the 10 mg MTA specimen significantly induced apoptosis when compared to control cells (p=0.043). Other specimens did not induce apoptosis (p>0.05). Our results verify the biocompatible nature of the examined specimens in terms of human mononuclear leukocytes apoptosis, and they should be confirmed by further in vivo studies in order to make a more reliable claim about the biological effects of examined specimens.
Keywords: Apoptosis; Calcium hydroxide; Mineral trioxide aggregate; Mononuclear leukocytes